SỰ PHÂN QUYỀN TRONG QUẢN LÝ RỪNG ẢNH HƯỞNG NHƯ THẾ NÀO ĐẾN QUYỀN SỞ HỮU TRONG QUẢN LÝ RỪNG CỘNG ĐỒNG: NGHIÊN CỨU TRƯỜNG HỢP Ở VÙNG CAO THỪA THIÊN HUẾ - Tuấn, Hoàng Huy (Nhà xuất bản Nông nghiệp, 2016)
Allocating forest to the local community is an early stage in the process of developing community forest management (CFM) in Vietnam. After forest allocation, villagers become forest owners. In this context, the study’s conceptual framework views the allocation of forest to community - i.e. the decentralization of forest management - as a form of political decentralization, and changes in property rights under forest decentralization as transfers of “bundles of rights”. This study was conducted in two villages in Hong Ha Commune, A Luoi district in the central Vietnamese Province of Thua Thien Hue. Kan Sam Village was selected as representative of a community that has been allocated forest by the state, and Pahy Village was selected as representative of a community that manages forest by customary law. Through these two villages in Thua Thien Hue’s uplands, the study made the following three key findings. First, that the allocation of forest to community was initiated by outsiders (local authorities and sponsors), but the lack of external support after allocating this forest means that the state has indirectly shifted the burden of cost of natural forest management to the community via this allocation process. The second finding is that changes in formal rights (legal rights) in the two villages vary, while informal rights (rights in practice) are similar. The forest decentralization has significantly changed formal rights over community forest. Before the allocation of forest, both villages only had formal rights of access. Since forest allocation, Pahy’s villagers have the same formal rights, while Kan Sam’s villagers have formal rights of access, withdrawal, management and exclusion. Contrary to formal rights, however, informal rights over community forest appear to be unchanged under forest decentralization. The third finding is that gaps between formal rights and informal rights over community forest always exist. There are three main causes of these gaps: lack of legal environment and support from local authorities; social and power relations (kinship); and differences in perception between older and younger generations.